Responsabilidade socioambiental: a divulgação de relatórios na América Latina - Calixto, Laura (2011)
This work aims to comparatively analyze the social and environmental information disseminated by Latin American companies in their reports. A content analysis was made of the social and environmental information disclosed by a sample of 226 organizations, in the period from 2004 to 2009, categorized by country, company, industry, and year. Voluntary guidelines by Global Reporting Initiative were used as a guide to analyze the content of annual reports, sustainability reports and 20F Forms, made available by organizations on their websites or by the stock exchanges on which they negotiate their actions. Most trading companies in the region do not provide social and environmental information in their annual reports or specific reports on the subject. Within the framework of multinationals operating in Latin America and that have been selected for this study, a greater concentration of those in Argentina, Chile and Peru were companies about whom more information was made available and environmental information in reports analyzed. Generally the level of adherence to the disclosure of social and environmental information using voluntary guidelines, by the Latin American countries that were analyzed during this study was found to be low, though companies established in Brazil were found to have a higher level of adherence to these guidelines. The theoretical reference indicated that various historical influences have contributed to the above result, such as the attention to social and environmental issues given by business leaders, in addition to the support of NGO’s that specialize in providing information on the subject. The Instituto Ethos de Empresas e Responsabilidade Social, and other entities, such as IBASE and GIFE performed an important role in the dissemination and professionalization of social and environmental information of Brazilian companies. In the other Latin American countries the subject is still incipient, although there are several local institutions that focus on corporate participation in the development and dissemination of reports focused on the subject. These reports only became widely available a few years ago. Companies that made up the sample of this study were among the largest in their respective countries. In the case of Brazil and Mexico, local industry has its own way of carrying out social and environmental initiatives, as well as disclosing the relevant information in specific reports. Regarding the development and dissemination of socialenvironmental information, the annual report has become the main source used for this purpose, followed by the sustainability report, published as part of the annual report or as a specific publication.